Game development toolkit design and implementation - Soh, Wei Jie (2018)
Serious games are games intended for more than simply entertainment, rather it is meant for learning skills and collecting data for researches. Serious games have many benefits that are unique, allowing for many different uses not only in education, but also in industries as a training tool for professionals. Serious game development requires more different discipline knowledge over a game intended for entertainment. This results in a longer schedule and more professional from different disciplines for the game development process than games meant for entertainment. This project aims to reduce the time required for the coding phase of the game development. A toolkit that consist of utility functions that are commonly used in serious games will be created in the Unity 3D game engine. This report will go into some of the details about the benefits of serious games and the advances in the tools that are used for game development. The subsequent sections will talk about the toolkit that was created in Unity.